Addressing the knowledge management "nightmare" for construction companies. Issue 2 (26th September 2020) - Vaz-Serra, Paulo; Edwards, Peter
Abstract : Purpose: Knowledge management presents a problem for the architecture, engineering and construction (AEC) industry, largely because of the industry's fragmented structure and project-driven nature. Construction companies may be involved in a variety of projects in different locations, each having its own knowledge requirements. Companies are also expected to be competitive, flexible and innovative, but introducing new knowledge management systems (KMSs) may represent a change that is beyond the organisation's capacity to undergo successfully, and thus becomes a "nightmare". The purpose of this paper is to propose and test a KMS solution that can help to facilitate the capture and application of important knowledge without introducing unnecessary changes in internal procedures for the organisation. Design/methodology/approach: Following a review of existing systems, and an interview survey of 22 managers in the Portuguese AEC industry (contractors, design consultants and project management consultants) a new IT-based construction KMS called ConstruKnowledge was developed. The KMS was tested, verified and validated in two Portuguese construction projects and assessed by 12 managers in the construction company undertaking those projects. Findings: The results of two pilot tests using ConstruKnowledge in two Portuguese construction projects demonstrate that its use can raise the levels of confidence in decision-making, and retaining knowledge; and that it serves to add value to the company. Practical implications: The Construknowledge KMS is an innovative contribution to the greater acceptance of KMSs in the construction industry. The system facilitates the effective and efficient development of an organisational KMS using basic Information and Communications Technology (ICT)-based collaboration tools. While undertaken in the context of the Portuguese industry, the KMS has a wider global potential for implementation and further development. Originality/value: The originality and value of this research are that it demonstrates how a KMS can be developed and then used in a construction company to capture and share knowledge without introducing additional constraints.